Differential preservation in a lacustrine fossil assemblage from the Cretaceous Bauru basin, Brazil - Oliveira, A. B. [UNESP]; Callefo, F.; Ricardi-Branco, F.; Batezelli, A.; Galante, D. (Elsevier, 2025)
Lakes are engaging environments for fossil diagenesis studies because of their potential for fossil preservation. One such example is the Upper Cretaceous São Carlos Shale, which corresponds to the paleolake, which is not documented anywhere in the Bauru Basin. The fossil assemblages were composed of plants, vertebrates, and invertebrates. Fossil diagenesis analyses were performed to understand the taphonomic conditions, chemical composition, and state of preservation of the constituents. Scanning electron microscopy (SEM) and electron detector spectroscopy (EDS) were used to determine the elemental composition and visualise framboidal pyrite inside the invertebrate fossils and the remains of biofilms intimately linked to them. Micro X-ray fluorescence (μ-XRF) mapping revealed the elemental distribution related to the original composition of carapace and vertebrate remains. X-ray diffraction of the bulk rock helped the mineralogical characterisation of the shales. Sulfate-reducing bacteria was found at the bottom of the lacustrine environment, resulting in the precipitation of pyrite via organic matter decomposition. Establishing low pH conditions promoted the partial dissolution of calcite carapaces, followed by apatite precipitation and the preservation of chitinous conchostracan carapaces. This change in the diagenetic conditions was not significant for charcoal preservation. In turn, teleost bones were preserved, likely because of their high P concentrations. Thus, even if controlled by low pH conditions, the chemical structural stability of bioapatite can be maintained during fossil diagenesis. The sources of these elements were likely runoff-reworked sediments derived from intermediate and felsic rocks on the paleolake. Although rich in vertebrate fossils, the assemblage studied shows a differentiated preservation for the Bauru basin, expanding the possibilities of the record for this exceptional basin of the South American plate.
Keywords: Bauru basin; Biofilms; EPS; Fossil diagenesis; Paleolake